Effect of Gasification Temperature on Synthesis Gas Production and Gasification Performance for Raw and Torrefied Palm Mesocarp Fibre - Najwa Hayati Abdul Halim; Suriyati Saleh; Noor Asma Fazli Abdul Samad (ASEAN Journal of Chemical Engineering, 2019)
Biomass gasification is widely used for converting solid biomass into synthesis gas for energy applications. Raw biomass is commonly used as feedstock for the gasification process but it usually contains high moisture content and low energy value which lowering synthesis gas production. Thus, torrefaction as a pre-treatment process is necessary in order to upgrade the properties of feedstock for producing more synthesis gas production and improving gasification performance. The objective of this work is to study the effect of gasification temperature on the synthesis gas production and gasification performance using raw and torrefied palm mesocarp fibre (PMF). The gasification process is conducted using bubbling fluidized bed using steam as gasifying agent. Based on experimental work, by increasing gasification temperature from 650 – 900 °C, the compositions of hydrogen and carbon monoxide gases were enhanced greatly while carbon dioxide and methane gases were decreased for both raw and torrefied PMF. In terms of gasification performance, synthesis gas yield for raw and torrefied PMF is increased from 0.91 to 1.23 Nm3/kg and 1.10 to 1.35 Nm3/kg respectively. Besides, lower heating value (LHV) of torrefied PMF is 0.04 MJ/Nm3 higher than raw PMF at 900 °C. The result showed that the percentage of cold gas efficiency (CGE) reached maximum of 67% for raw PMF while carbon conversion (CC) at 85.6% for torrefied PMF at a gasification temperature of 900 °C. The higher CC obtained by torrefied PMF is because of the increment of carbon content from 45.2% to 53.7% as a result of torrefaction. Gasification temperature of 800 °C showed the best performance of the PMF gasification since the maximum performances of LHV is achieved and started to decrease once the gasification temperature is operated beyond 800 °C.